2013
DOI: 10.1002/hep.26229
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Neurocognitive Function in Responders to an Antiviral Therapy for Chronic Hepatitis C

Abstract: Earlier studies have suggested neurocognitive impairment in patients with chronic hepatitis C virus (HCV) infection even before liver cirrhosis has developed. Since these deficits might be reversible after successful antiviral therapy, we analyzed the long‐term course of neurocognitive parameters in HCV patients with and without successful virus elimination by an interferon‐based antiviral treatment. In a multicenter study including 168 HCV patients receiving antiviral therapy (peginterferon alpha‐2b and ribav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 27 publications
1
40
1
Order By: Relevance
“…Two studies have reported improvement of the neurocognitive function in patients with HCV after successful antiviral therapy, suggesting that benefits on the neurocognitive dysfunction may be an additional consideration for prescribing antiviral therapy in patients with chronic hepatitis C [77,78].…”
Section: Neurocognitive Dysfunctionmentioning
confidence: 97%
“…Two studies have reported improvement of the neurocognitive function in patients with HCV after successful antiviral therapy, suggesting that benefits on the neurocognitive dysfunction may be an additional consideration for prescribing antiviral therapy in patients with chronic hepatitis C [77,78].…”
Section: Neurocognitive Dysfunctionmentioning
confidence: 97%
“…Many of the manifestations of HCV‐related mixed cryoglobulinemia can resolve following successful HCV treatment, although patients with significant renal or neural injury may not recover fully after eradication of HCV infection . In the HCV‐monoinfected population, eradication of HCV following anti‐HCV therapy may reduce the risk of developing type II diabetes mellitus, renal and cardiovascular events, and neurocognitive dysfunction …”
mentioning
confidence: 99%
“…A recent study regarding HCV viral clearance did not determine metabolite concentrations in SVR, but did measure neurocognitive performance in these patients [42]. Although previous studies yielded conflicting results regarding viral clearance and neurocognitive improvement, this study had a larger sample size and the neurocognitive tests were performed at least 12 months after therapy ended.…”
Section: Metabolic Abnormalitiesmentioning
confidence: 99%